Genotype × Environment Interaction and Stability Analysis for Root Yield in Sweet Potato [Ipomoea batatas (L.) Lam] - Ebem, Emmanuel C.; Afuape, Solomon O.; Chukwu, Samuel C.; Ubi, Benjamin E. (Frontiers in Agronomy, 2021)
Sweetpotato breeding in Africa more especially in Nigeria has mainly focused on improving productivity on farmers’ fields and for fresh root consumption. In order to target the breeding program the study was conducted to estimate the magnitude of genotype x environment interaction (G x E) and to select stable and high yielding sweetpotato genotypes for fresh root yield and root cylas severity in two locations, and to identify the most discriminating and representative test environments in Nigeria. Forty one genotypes were evaluated across four diverse environments using a 4 × 11 simple lattice design with three replications. Data were collected on total number of roots per plant, number and weight of marketable roots per plant, fresh root yield, root cylas severity and were subjected to analysis of variance using the Generalised Linear Model procedure of SAS 9.2 where genotype was treated as a fixed factor and replication treated as random variable. Stability analysis was conducted using Genotype and Genotype x Environment Interaction (GGE) bi-plot. Environment, genotype and G × E interaction variances were highly significant (p ≤ 0.001) among the assessed agronomic traits. Moreover, the analysis of variance revealed highly significant (p ≤ 0.001) differences among genotypes, environments and G × E interaction effects for all the studied traits. The GGE biplot analyses identified the following promising genotypes: G13, G11 and G14 that possess both high mean root yield and high stability, closest to the ideal genotype for root performance and consistency of performance across environments. This study provides valuable information that can be utilised in a breeding programme to ameliorate local clones of sweet potato in Nigeria.